2020
DOI: 10.21203/rs.3.rs-39395/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatio-temporal Characteristics of Frictional Properties on the Subducting Pacific Plate Off the East of Tohoku District, Japan Estimated from Stress Drops of Small Earthquakes

Abstract: Abstract The east coast of the Tohoku district, Japan has a high seismicity, including aftershocks of the 2011 M9 Tohoku earthquake. We analyzed 1142 earthquakes with $4.4 \le M_{W} \le 5.0$ that occurred in 2003 through 2018 and obtained spatio-temporal pattern of stress drop on the Pacific Plate that subducts beneath the Okhotsk Plate. Here we show that small earthquakes at edges of a region with a large slip during the 2011 Tohoku earthquake had high values of stress… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Consistent interpretations by Yamada et al. (2021) associated high stress drop values with a gradual weakening of the shear strength due to stress concentration during the coseismic slip of the mainshocks. Following the temporal decrease, the median truenormalΔσ^ $\hat{{\Delta}\sigma }$ values then increase in the subsequent months, consistent with fault zone healing and an increase in fault strength (e.g., Goebel et al., 2015; Moyer et al., 2018; Vidale et al., 1994).…”
Section: Discussionsupporting
confidence: 83%
“…Consistent interpretations by Yamada et al. (2021) associated high stress drop values with a gradual weakening of the shear strength due to stress concentration during the coseismic slip of the mainshocks. Following the temporal decrease, the median truenormalΔσ^ $\hat{{\Delta}\sigma }$ values then increase in the subsequent months, consistent with fault zone healing and an increase in fault strength (e.g., Goebel et al., 2015; Moyer et al., 2018; Vidale et al., 1994).…”
Section: Discussionsupporting
confidence: 83%
“…A ratio of 1.27 corresponds to a rupture velocity of about 0.75 vs ${v}_{s}$, so we set k P as 0.33 and k S as 0.26 (Kaneko & Shearer, 2014) to compute the stress drops (4). Other studies have found similar vr/vs ${{v}_{r}/v}_{s}$ based on P / S corner frequency ratios in subduction zones (Yamada et al., 2021). Note however that this ratio is an average in space and time, and therefore the scattering can be explained by varying rupture velocities and geometries among events.…”
Section: Resultsmentioning
confidence: 62%
“…Some authors have found a degree of correlation between stress drops of microearthquakes and the coseismic slip areas of large earthquakes: stress drops were sometimes found to be high around past rupture zones and low within them (Yamada et al., 2021), although that correlation is ambiguous (Allmann & Shearer, 2007; Shearer et al., 2006). Similarly, Hardebeck and Aron (2009) found that stress drops of earthquakes in and around locked zones were higher on average than those on creeping portions of the Hayward fault (California) at similar depths, suggesting a link to coupling.…”
Section: Introductionmentioning
confidence: 99%